Management and Impact of Electronic Commerce in Hotels in Tabasco - SÁNCHEZ TRINIDAD, Rosa del Carmen; CASTILLO MÉNDEZ, Rocío del Carmen; MARQUEZ AMARO, Raymundo; AGUIRRE ANDRADE, Antonio; SÁNCHEZ CRUZ, Samantha; SÁNCHEZ TRINIDAD, Adriana del Carmen; DE DIOS DOMINGUEZ, Wilber (Journal of Environmental Management and Tourism; Vol 13 No 6 (2022): JEMT, Volume XIII, Issue 6(62), Fall 2022, 2022)
The research work meets viable characteristics and conditions for carrying out this study, since its development consists of observing the management and impact of electronic commerce in the services provided in the selected companies. This implies, in principle, carrying out a series of on-site visits to the hotels with the aim of interviewing those responsible for the reservations departments and any other area that sells a service through this channel.